Akibat Perbuatan Melawan Hukum dalam Pelelangan Objek Hak Tanggungan (Putusan Nomor 23/PDT.G/2020/PN.KLA) - Veryantoyo Eka Yunanda; Arman Nefi (Jurnal Supremasi, 2023)
The auction for the execution of the mortgage right can be held by the creditor as the holder of the mortgage right for the defaulting debtor, but there are several important aspects in fulfilling a person who can be declared in default or not, this aims to avoid activities or conditions of illegal acts. This study discusses the consequences of an unlawful act in the auction of mortgage objects. In answering the problems in this research, a normative juridical approach is used with the type of analytical descriptive research and uses a qualitative data analysis method. The results of the analysis on the Kalianda District Court Decision No. 23/Pdt.G/2020/PN.Kla stated that there were circumstances that caused debts to be uncollectible immediately and all at once, paying attention to the unexpired term of the agreement is a determining aspect of whether a person can be declared in default and the value of the collateral that is greater than the debt causes the debtor to be in a position not yet eligible to be declared in default. An unlawful act is a determining aspect that can cancel the outcome of the execution of the mortgage due to violating the subjective rights of other people as the owner of the land object of the mortgage, because it violates the subjective rights of other people as the owner of the mortgage object land, causing losses to the debtor because the mortgage object is auctioned off or there is a causal relationship between the error and the loss suffered.